Research on Methods for Developing Writing Skills in Teaching a Foreign Language - Bazarbayeva Aida Askarovna (Scientific Research and Experimental Development, 2025)
The development of writing skills plays a crucial role in foreign language teaching as it enhances learners’ ability to structure thoughts, communicate effectively, and integrate other language competencies. This article explores effective pedagogical methods for improving writing skills in foreign language classrooms. The research focuses on communicative and task-based approaches, process writing, and the use of digital technologies. The findings highlight the importance of integrating writing with reading, speaking, and critical thinking activities. Practical recommendations for teachers are provided to foster student motivation and creativity.